Visceral leishmaniasis in border areas: Clustered distribution of phlebotomine sand flies in Clorinda, Argentina - Salomón, Oscar Daniel (2009)
Three years after the first report of Lutzomyia longipalpis in Clorinda, Argentina, a border city near Asunción, Paraguay, the city was surveyed again. Lu. longipalpis was found clustered in the same neighbourhoods in 2007 as in 2004, even though the scattered distribution of canine visceral leishmaniasis was more related to the traffic of dogs through the border.